Composted palm waste as an alternative of coco peat in growing media: effects on growth and nutritional status of Lily cut flower (Lilium spp.) - Sajad Heidari (University of Birjand, 2021)
Purpose: A greenhouse experiment was conducted to evaluate the effect of the mixture of different growing media (palm trunk: resulted from palm trunk only; palm tree: resulted from all palm organs; coco peat; perlite; reused coco peat) on growth and nutrient uptake of lily cut flower. Research method: Treatments including two cultivars (Tiber and Candy Club) and eleven growing media compositions were set up in a factorial experiment based on a completely randomized design. Findings: The Control showed the highest leaf surface area, bulb depletion rate, and Mg content, while the higher plant height and the leaves number were observed in 40% and 80% palm trunk treatments, respectively. Furthermore, the 40% palm trunk resulting in a higher Fe content. The highest bud's number, K, Cu, and Mn content measured in Candy Club, which was cultivated on 20% palm tree treatment, that increased by an average of 10.1%, 15.8%, 67.4%, and 54.3%, respectively compared to the control. The Candy Club has grown on control showed the highest values of the reproductive organ length, N, and P concentration. The highest Ca content was obtained after the Tiber's cultivation in the 80% palm trunk. Research limitations: No limitations were founded. Originality/Value: Because of the low cost, availability, and extensive cultivation area of date palm in Iran and over the world, palm wastes has a great potential to be used as an eco-friendly horticultural substrate mixture to substitute coco peat in lily soilless culture.